PERANCANGAN FLYBACK CONVERTER UNTUK CATU DAYA DRIVER MOTOR BLDC ( BRUSHLESS DIRECT CURRENT ) - Agus Mahendra; Sapril Sapril; Maryantho Masarrang (Foristek, 2019)
Flyback Converter is an electronic circuit that can increase the output voltage value, the voltage value can be adjusted by changing the value of the duty cycle. This Flyback Converter will be controlled by the Pulse Width Modulation method as the output voltage setting and this research is equipped with a feedback function as monitoring and control of Input Pulse Width Modulation. This designed flyback converter aims to provide an isolated power supply as a power source for Brushless Direct Current Motor drivers, and this research was conducted to analyze how much power the flyback converter can produce to be able to supply Brushless Direct Current Motor drivers. The results of the analysis obtained in the research Design of flyback converter for power supply of BLDC (Brushless Direct Current) motor driver that is flyback converter is given an input voltage of 31 VDC and output voltage of 15 VDC, rheostat load with a capacity of 39 Ohm, a frequency of 31 KHz in the form of a box wave duty cycle reaches 70%. Flyback converter designed to produce maximum power of 49.6 watts on 70% duty cycle testing.